Medium-term outcomes and complications after total replacement of the temporomandibular joint. Prospective outcome analysis after 3 and 5 years. Issue 5 (May 2015) - Gruber, E.A.; McCullough, J.; Sidebottom, A.J.
Abstract In this prospective analysis, we assess the medium-term benefits, efficacy, and safety of the TMJ Concepts joint replacement system in the United Kingdom. Outcome measures of pain, maximum mouth opening, and diet were recorded preoperatively and at intervals up to 3 and 5 years. All patients who had replacement temporomandibular joints (TMJ) within a 6-year period were included. A total of 58 patients (84 joints) were followed up for 3 years (mean age 47, range 19–72) and 26 (42 joints) for 5 years (mean age 46, range 27–70). The female to male ratio was 52:6 at 3 years and 23:3 at 5 years. The most common diagnosis was degenerative disease, and the mean number of previous TMJ procedures was 2.4 (range 0–14). There were significant improvements in pain scores (7.4 reduced to 0.6 at 3 years and 0.8 at 5 years), maximum mouth opening (21.0–35.5 mm at 3 years and 23.8–33.7 mm at 5 years), and dietary scores (4.1–9.7 at 3 years and 3.7–9.6 at 5 years). Revision operations were required in 2 patients (not included in the outcome data) for biofilm infection of the prosthesis secondary to local infection in the head and neck. One patient had weakness of the temporal branch of the facial nerve that needed correction. TMJ replacement is an effective form of management for an irreparably damaged joint, particularly in cases of ankylosis. It lessens pain and improves function with minimal long-term morbidity.